IMPACT OF POPULATION, TRADE OPENESS, EDUCATION, LIFE EIMPACT OF POPULATION, TRADE OPENESS, EDUCATION, LIFE EXPECTANCY AND GROSS CAPITAL FORMATION ON THE ECONOMY OF INDIAN SUB-CONTXPECTANCY AND GROSS CAPITAL FORMATION ON THE ECONOMY OF INDIAN SUB-CONTINENT - Javed, Sarfaraz; Khan, Mohammad Shahfaraz; Farooqi, Ataur Rahman (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the impact of population, trade openness, education, life expectancy and gross capital formation on the economy of Indian sub-continent.This study made use of quantitative research design andsecondary data on population, trade openness, education, life expectancy, gross capital formation and GDP of India, Pakistan, Sri Lanka and Bangladesh gotten from world bank database from 1990-2017 was used. The outcome variable was GDP while the predictor variables were population, trade openness, education, life expectancy and Gross Capital Formation (GCF). The data was analyzed using Eviews 9.0 and statistical methods such as Pearson Correlation, Fixed and Random Model and Hausman Tests were used to test the hypotheses. The finding of this study shows that Population, Life Expectancy and Trade openness significantly influence economy of India while education and Gross Capital formation did not. Also, Gross Capital formation positively significantly impact economy of Pakistan while Population, Life Expectancy, Trade Openness and education did not significantly impact the economy of Pakistan. In Sri Lanka, Population, Life Expectancy, Trade Openness, Gross Capital Formation and education did not significantly impact the economy. In Bangladesh, Population, Life Expectancy, Trade openness, education for all, education for men and women significantly influence economy. The result of the fixed and random effect shows that population effect across Bangladesh and Pakistan is positive and significant and the population effect of India is negative while that of Sri Lanka is not significant. Gini education for all is positive and significant in India and Sri Lanka which implies that education for all positively impact economy of India and Sri Lanka while education for all is negatively significant in Pakistan and not significant in Bangladesh. Many of the previous research works were centered on India. Very few studies had been carried out on Indian- subcontinents with respect to the variables considered in this study.This study examines the overview of previous related research studies and also examine the impact of the predictor variables on economic growth in the selected 4 countries selected from the Indian sub-continents using Fixed and Random Model and Hausman Tests.